The Influence Of Financial Literacy, Ease Of Access, And Cost Efficiency On The Financial Optimization Of Users Of Seabank Digital Services - Umami, Reza; Ryanto, Fuad Ramdhan (UNIVERSITAS PAKUAN, 2024)
Research Objective: This study investigates the influence of financial literacy, ease of access, and cost efficiency on the financial optimization of Sea Bank digital service users. Design/Methodology/Approach: Employing a quantitative methodology within an associative framework, this research collected data through a digital questionnaire distributed online. The study population comprised active Sea Bank users in Indonesia, estimated at approximately 10 million. A purposive sampling technique was used to select 100 participants based on specific qualifications, such as their level of engagement and utilization of Sea Bank services. Data were analyzed using SPSS version 26. Research Findings: (1) Financial literacy positively and significantly impacts financial optimization. (2) Ease of access positively and significantly influences financial optimization. (3) Cost efficiency positively and significantly affects financial optimization. (4) Collectively, the three variables exert a positive and significant effect on financial optimization. Theoretical Contribution/Originality: This research contributes to financial knowledge by emphasizing the role of monetary literacy within the context of digital banking platforms, particularly Sea Bank. By proposing an analytical model linking financial literacy, ease of access, and cost efficiency to financial optimization, the study offers valuable insights for the existing literature and serves as a foundation for future research. The findings also reinforce efforts to promote financial education and awareness in society, while paving the way for further exploration of other factors that may influence financial optimization among digital banking users.